Tuning π-Acceptor/σ-Donor Ratio of the 2-Isocyanoazulene Ligand: Non-Fluorinated Rival of Pentafluorophenyl Isocyanide and Trifluorovinyl Isocyanide Discovered - Mason D. Hart; John J. Meyers; Zachary A. Wood; Toshinori Nakakita; Jason C. Applegate; Nathan R. Erickson; Nikolay N. Gerasimchuk; Mikhail V. Barybin (Molecules, 2021)
Isocyanoazulenes (CNAz) constitute a relatively new class of isocyanoarenes that offers rich structural and electronic diversification of the organic isocyanide ligand platform. This article considers a series of 2-isocyano-1,3-X2-azulene ligands (X = H, Me, CO2Et, Br, and CN) and the corresponding zero-valent complexes thereof, [(OC)5Cr(2-isocyano-1,3-X2-azulene)]. Air- and thermally stable, X-ray structurally characterized 2-isocyano-1,3-dimethylazulene may be viewed as a non-benzenoid aromatic congener of 2,6-dimethyphenyl isocyanide (2,6-xylyl isocyanide), a longtime “workhorse” aryl isocyanide ligand in coordination chemistry. Single crystal X-ray crystallographic Cr–CNAz bond distances, cyclic voltametric {E1/2(Cr0/1+)}, 13C NMR {δ(13CN), δ(13CO)}, UV-vis {dπ(Cr) → pπ*(CNAz) Metal-to-Ligand Charge Transfer}, and FTIR {νN≡C, νC≡O, kC≡O} analyses of the [(OC)5Cr(2-isocyano-1,3-X2-azulene)] complexes provided a multifaceted, quantitative assessment of the π-acceptor/σ-donor characteristics of the above five 2-isocyanoazulenes. In particular, the following inverse linear relationships were documented: δ(13COtrans) vs. δ(13CN), δ(13COcis) vs. δ(13CN), and δ(13COtrans) vs. kC≡O,trans force constant. Remarkably, the net electron withdrawing capability of the 2-isocyano-1,3-dicyanoazulene ligand rivals those of perfluorinated isocyanides CNC6F5 and CNC2F3.